2011
DOI: 10.1016/j.jtcvs.2010.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the elastic modulus of ascending thoracic aortic aneurysm at different ranges of pressure using uniaxial tensile testing

Abstract: This study provides new data on the elastic modulus in the physiologic and hypertensive range that can be used in computational analysis and the design of bench-top models. The accuracy of computational analysis and bench-top models strongly depends on the knowledge of the elastic properties of the aortic wall. The mechanical properties presented in this study, with specific values for 2 locations (greater and lesser curvature) and 2 directions (circumferential, longitudinal), will increase our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 18 publications
(22 reference statements)
3
73
0
Order By: Relevance
“…During preconditioning and extension, load and displacement were continuously recorded with a sampling frequency of 10 Hz. It is worth noting that the adopted cross-head speed is the one proposed in [36,37].…”
Section: Mechanical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…During preconditioning and extension, load and displacement were continuously recorded with a sampling frequency of 10 Hz. It is worth noting that the adopted cross-head speed is the one proposed in [36,37].…”
Section: Mechanical Testsmentioning
confidence: 99%
“…In particular, some studies move from the presentation of new tools in imaging analysis to evidence possible alterations in the morphology and in the micro-structure of the diseased aortic tissues [26,27]. Other studies focus on the use of mechanical tests (uniaxial and biaxial tensile tests) to evaluate and compare mechanical properties of both healthy and diseased tissues [28][29][30][31][32][33] and, at the same time, to investigate factors which can influence tissue properties like location and orientation [23,[34][35][36][37], patient age [30,38,39], patient sex [39,40], and presence of concomitant pathologies [25,33,36,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this study, the systolic AsAA meshes were transformed to obtain the unpressurized geometry using the following approach. Treating the AsAA as a thin-walled cylindrical pressure vessel as often done (8,12,18,20,23), the systolic wall tension in the circumferential (systolic hoop tension), t c sys , and axial directions, ta sys , are given by the Law of Laplace:…”
Section: Asaa Fe Modelingmentioning
confidence: 99%
“…Tensile strength of the aortic wall is not homogenous and shows directional changes; most studies have consistently shown that the aortic wall is less strong in the longitudinal direction [20,21] with preferential rupture perpendicular to its long axis when stress is applied in both directions [22]. Moreover, Khanafer et al studied tissue samples of human ascending aorta aneurysm and found that aneurysm diameter was more strongly correlated with increased longitudinal than circumferential wall stress [23]. All these findings suggest that longitudinal wall stress may be as important as circumferential stress in the pathogenesis of aortic dissection and may be the leading cause of a transverse tear along the long axis of the aorta.…”
Section: Axial Downward Motion Of Aorta After Pears and Risk Of Dissementioning
confidence: 99%